Kewirausahaan Sebagai Pemanfaatan Dana Program Mapalansi oleh Pihak Karyawan Universitas Al-Irsyad Cilacap - Lia Ernawati; Mika Tri Kumala Swandari; Dani Setyawan; Rizky Nugroho; Herlin Natasya; Salsa Fabillah; Angelia Puspitasari Anuar (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
In the midst of the Covid-19 pandemic, Indonesia was hit by an increase in several goods (inflation_namely cooking oil). From an Indonesian economic growth data that came from the Central Statistics Agency (BPS) before and after the Covid-19 pandemic. Impacted by Covid-19, the level of economic growth Indonesia is relatively stable, but due to the impact of the Covid19 pandemic in early 2020, the economic growth rate of the Indonesian people has decreased very significantly, so this community service activity is based on these problems and provides solutions in the form of financial assistance and entrepreneurship training.